Effects of land use/cover changes on Tehran’s air quality - Abutaleb Sabr; Mazaher Moeinaddini; Hossein Azarnivand (علوم محیطی)
Introduction: In recent decades, air quality change and its risks are correlated with the expansion of urban and industrial areas and other land-use changes. One of the important effects of land use/cover changes (LUCC) is wind erosion and as a result, an increase in particulate matter (PM) concentration in residential areas. For this reason, the effects of LUCC on PM concentration in Tehran’s airshed was studied. Material and methods: Data on LUCC and landscape metrics were studied in the years 1985, 2000 and 2014. Then, the relationship between LUCC and PM concentration in Tehran was investigated by trend analysis methods. To find the most important wind directions with strong effects on Tehran’s air quality, conditional probability function (CPF) and directional relative strength (DRS) were used. Results and discussion: LUCC results showed that the area of agricultural land-use has been expanded from 1985 to 2000, yet decreased from 2000 to 2014. The trend was vice versa for barren lands during the mentioned time periods. In addition, the urban area has increased in the whole period. The landscape metric results showed that landscape patches became smaller and the landscape has been fragmented. The results of the PM10 concentration trend analysis revealed that it has been increased dramatically since 2007. Comparison of the average concentration of PM10 before and after 2007 showed a significant difference. The results of CPF and DRS illustrated that no specific wind direction was detected before 2007, but afterwards both increased in specific directions (south to west), which is compatible with most LUCC and fragmented areas in these directions. Conclusion: Our results showed that specific wind directions may lead to an increase in the PM10 concentration which is compatible with LUCC directions. Therefore, LUCC could be a significant reason for the increase in PM10 concentration in Tehran.